Crystallization and preliminary X-ray diffraction analysis of importin-alpha acomplexed with NLS peptidomimetics - Fontes, MRM; Teh, T.; Riell, R. D.; Park, S. B.; Standaert, R. E.; Kobe, B. (Elsevier B.V., 2005)
Importin-alpha is the nuclear import receptor that recognizes cargo proteins with nuclear localization sequences (NLSs). Tile study of NLS peptidomimetics can provide a better understanding of the requirements for the molecular recognition of cargo proteins by importin-alpha, and potentially engender a large number of applications in medicine. Importin-a was crystallized with a set of six NLS peptidomimetics, and X-ray diffraction data were collected in the range 2.1-2.5 angstrom resolution. Preliminary electron density calculations show that the ligands are present in the crystals. (c) 2005 Elsevier B.V All rights reserved.
Keywords: crystallization; X-ray crystallography; importin-alpha; karyopherin-alpha; nuclear localization sequence; NLS peptidomimetic ligand